2015
DOI: 10.1038/nsmb.3040
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding drives substrate capture in an ECF transporter by a release-and-catch mechanism

Abstract: ECF transporters are a family of active transporters for vitamins. They are composed of four subunits: a membrane-embedded substrate-binding subunit (EcfS), a transmembrane coupling subunit (EcfT), and two ATP-binding cassette ATPases (EcfA and EcfA′). We have investigated the mechanism of the ECF transporter for riboflavin from the pathogen Listeria monocytogenes, LmECF–RibU. Using structural and biochemical approaches we find that ATP binding to the EcfAA′ ATPases drives a conformational change that dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 50 publications
(107 reference statements)
5
78
1
Order By: Relevance
“…In a recent paper, the structure of the riboflavin-binding subunit Lmo1945 (EcfS or RibU) of the riboflavin uptake system was reported (25). Physiological experiments showing that Lmo1945 is indeed involved in riboflavin transport were not performed (25), and we set out to validate this anticipated function.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, the structure of the riboflavin-binding subunit Lmo1945 (EcfS or RibU) of the riboflavin uptake system was reported (25). Physiological experiments showing that Lmo1945 is indeed involved in riboflavin transport were not performed (25), and we set out to validate this anticipated function.…”
Section: Resultsmentioning
confidence: 99%
“…We took advantage of the observations that while isolated S subunits co-purify with their respective transport substrate [1012, 15, 21, 37] complete ECF transporters do not [1518, 25, 37, 38]. We previously demonstrated that the homologous ECF riboflavin transporter from Listeria monocytogenes , LmECF-RibU, captures the riboflavin transport substrate by a “release and catch” mechanism [37]. In this system, ATP binding drives a conformational change that dissociates the EcfS subunit from the EcfAA′T ECF module.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies indicated that S subunits for different vitamins compete for transport by the ECF module and such competition is enhanced in the presence of the substrate [9, 37, 55]. These observations suggest that the apo and substrate-bound conformations of EcfS have different affinities for the ECF module.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important question that still needs to be addressed is in which conformational state the ECF module interacts with the S‐component. It needs to be demonstrated whether the toppling of the S‐component might depend on the hydrolysis of ATP as it has been postulated by alternative models …”
Section: Energy‐coupling Factor and Adenosine 5′‐triphosphate‐bindingmentioning
confidence: 99%